2020
DOI: 10.1111/tbj.14018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mastectomy for breast cancer on spinal curvature: Considerations when treating patients with scoliosis

Abstract: Objective Mastectomy has been shown to influence body posture in women; however, there are limited data outlining changes in spine curvature after mastectomy in patients with scoliosis. We sought to quantify changes in spine curvature after mastectomy for breast cancer. Methods We conducted a retrospective review of 62 patients with scoliosis who underwent mastectomy for breast cancer at a single institution between 1995 and 2018. Preoperative and postoperative radiographs were used to measure Cobb angles to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…5 41 42 These changes are particularly relevant in patients with preexisting spine disorders. Gutkin et al 43 investigated 62 patients with scoliosis and found a significant increase of spine curvature after mastectomy. Immediate breast reconstruction significantly reduces the amount of change in spinal alignment after unilateral mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…5 41 42 These changes are particularly relevant in patients with preexisting spine disorders. Gutkin et al 43 investigated 62 patients with scoliosis and found a significant increase of spine curvature after mastectomy. Immediate breast reconstruction significantly reduces the amount of change in spinal alignment after unilateral mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The mass of breast removed significantly correlated with the difference in Cobb angle in nine patients who received unilateral mastectomy. However, laterality of mastectomy was not related to the side of shift in scoliosis curvature [17]. In a study assessing chest radiographs before and after delayed breast reconstruction, the difference was statistically significant and the average change in Cobb angle was 4.3 [16].…”
Section: Plos Onementioning
confidence: 94%
“…In addition, breast cancer survivors are at elevated risk for spinal abnormalities (e.g., scoliosis) because of post-treatment changes in posture and bone health. Other authors [13][14][15][16][17][18][19] have evaluated the relationship between breast cancer surgery and spine deformity by means of radiological assessment. However, the findings of these studies are inconsistent, and most studies employed chest radiographs or dual energy X-ray absorptiometry to identify only thoracic or lumbar regions of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…Among the recently discussed breast cancer issues is the postural control assessment in women after mastectomy [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. A review of the above-mentioned publications indicated that the undertaken research was concerned with the impact of mastectomy on body static conditions [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and body posture of women who had received mastectomies [ 7 , 10 , 18 , 19 ,…”
Section: Introductionmentioning
confidence: 99%
“…A review of the above-mentioned publications indicated that the undertaken research was concerned with the impact of mastectomy on body static conditions [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and body posture of women who had received mastectomies [ 7 , 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] and also the impact of external breast prostheses on postural control in women after mastectomies [ 11 , 12 , 14 , 32 ]. The results of several scientific reports indicate that mastectomies may cause body posture disorders such as asymmetry in the trunk in the frontal plane [ 18 , 21 , 42 , 43 , 44 , 45 , 46 ,...…”
Section: Introductionmentioning
confidence: 99%